EXAMINING CONSTITUTIONAL AWARENESS AND STRENGTHENING JUDICIAL INTEGRITY - Sukmariningsih, Retno Mawarini (Faculty of Law, Universitas Sebelas Maret, 2018)
This article is aimed to review constitutional awareness and decision-strengthening practice in judicial institutions. As it turns out in practice, however, the legal decisions are still debatable in reality. The practice of abuse of authority in the judiciary tends to damage the pillars of the judiciary and result in a decline in trust and certainly the authority of the judiciary against society. It is a normative legal research (doctrinal research). The approach used is qualitative analysis and the application of legislation. The results of research indicate that the strengthening of the judge’ decision can be started from the quality of decision through a comprehensive and mind-opened dimension, so that it is necessary to increase the pattern of development not only by the judges but also by all relevant stakeholders such as the Secretariat General and the Registrar Apparats. The focus of development is not only about knowledge but also it was conducted from all aspects such as mental and spiritual development that conducted continuously. The consequences of providing sufficient budget to realize it and in its implementation are conducted with full responsibility.